Dynamic Coefficients Identification of Water-Lubricated Hybrid Bearings Used in High-Speed Spindles with Different Excitation Methods - Lin Wang; Xianzhi Xiong; Hua Xu (Shock and Vibration)
Rotor stability and rotation accuracy, which are highly dependent on the dynamic coefficients of supporting hybrid bearings, are two important issues of high-speed water-lubricated spindles. To improve the spindles’ performance, the dynamic coefficients of high-speed water-lubricated hybrid bearings were experimentally identified by the noncontact harmonic excitation method and the additional unbalance excitation method, respectively. Comparisons between experimental results and theoretical predictions were made. The experimental technique and the identification model were validated to be effective. Besides, the influence of supply pressure and rotating speed on dynamic coefficients was also presented. As for different operating conditions, valuable guides were provided to investigate the dynamic performance of high-speed and ultra-high-speed spindles.